High-powered investing all-in-one for dummies - Best, Jason W. (Hoboken, NJ : John Wiley & Sons, 2014)
Looking for help making smarter, more profitable high-end investment decisions? This resource arms you with an arsenal of advanced investing techniques, and gets you up to speed on using business fundamentals and technical analysis to make smarter decisions and maximize your returns.
Getting started with high-powered investing. What every investor should know ; Playing the market : stocks and bonds ; Getting to know mutual funds and ETFs ; All about annuities -- Futures and options. Futures and options fundamentals ; Being a savvy futures and options trader ; Basic trading strategies ; Advanced speculation strategies -- Commodities. Getting an overview of commodities ; Adding commodities to your portfolio ; The power house : making money in energy ; Pedal to the metal : investing in metals ; Down on the farm : trading agricultural products -- Foreign currency trading. Your Forex need-to-know guide ; Major and minor currency pairs ; Gathering and interpreting economic data ; Advice for successful Forex trading ; Putting your trading plan in action -- Hedge funds. Getting the 411 on hedge funds ; Taking the plunge with hedge funds ; A potpourri of hedge fund strategies ; Evaluating hedge fund performance -- Emerging markets. Introducing emerging market investing ; A guided tour through the world's emerging markets ; Picking bonds, stocks, and mutual funds in emerging markets ; High finance in emerging markets -- Value investing. An introduction to value investing ; A value investor's guide to financial statements ; Using ratios as a valuation tool ; Valuing a business -- Socially responsible investing. Making your investments match your values ; The socially responsible enterprise : evaluating companies ; Introducing the Islamic capital market ; Managing assets in Islamic investments -- Crowdfund investing. Getting the lowdown on crowdfund investing ; Evaluating crowdfund investing opportunities ; Committing your capital and adding value -- Technical analysis. Wrapping your brain around technical analysis ; Bars and bar reading ; Charting the market with candlesticks ; Seeing patterns and drawing trendlines ; Transforming techniques into trades.
"10 books in 1"--Cover.
Includes index.
Business Administration
Keywords: Investments; Speculation